This is Adaptation: The Elimination of Subsidies Under the National Flood Insurance Program - Fox, Sarah (Columbia Journal of Environmental Law, 2019)
The oceans are rising. Amid any remaining debates about climate change and its relation to human activity, this fact appears unassailable. “Records and research show that sea level has been steadily rising at a rate of 1 to 2.5 millimeters (0.04 to 0.1 inches) per year since 1900,” and since 1992, new methods of measurement show a “rate of rise of 3 millimeters (0.12 inches) per year.” Changing climatic conditions have led to an increase in the temperature of ocean water and consequent expansion in its volume. That rise in temperature has also led to the melting of polar ice caps, adding water to the ocean. At the same time, the changing climate has resulted in more frequent extreme hurricanes. And higher sea levels increase the risk these storms pose to coastal communities at a time when such communities are growing rapidly in the United States. A series of powerful storms—and the costs they have exacted—have vividly demonstrated the consequences of this dangerous trifecta over the past decade. ... The reality of moving away from subsidies may therefore raise complicated social and legal issues. Reliance-based impacts, and any legal responsibilities that they create with regard to the elimination of subsidies, must be fleshed out and considered. The controversy over recent amendments to the NFIP provides a helpful framework for this consideration. Many purchased homes in the floodplain in reliance on the availability of subsidies, and possible revocation of those subsidies was met with public outcry. But an analysis of potential government obligations based on contract law, regulatory takings doctrine, due process, or environmental justice shows that none of these frameworks obligate a government to continue its provision of subsidized flood insurance. As governments attempt to make up for poor decisions in the past, assessing how much change communities can be expected to take on at a time becomes enormously important. Clarifying that this question is one of policy choice rather than government obligation, however, may provide support to policymakers tasked with implementing needed changes. This struggle to reverse course from a subsidized way of life is just one of the hard first steps that policymakers and their constituents will increasingly confront in the face of a changing climate. This is adaptation.